Water striders (Gerris sp) and its potential as mercury bioindicators in Lake Taliwang, West Sumbawa, Indonesia - A. Rahman; Muhammad Wahyu Setiyadi (Jurnal Pijar Mipa, 2022)
This study aims to determine the mercury accumulation in Gerris sp and its potential as a bioindicator. This type of research is experimental research. This research was conducted at Lake Taliwang and the UGM Integrated Research and Testing Laboratory. The sampling point in this study was determined based on the distance to the pollutant source. It was divided into station 1 (inlet), an area close to the pollutant source, and station 2 (outlet), far from the pollutant source. There are 3 test tests: the accumulation of mercury in water and sediment, mercury in the gerris, and the gerris as a bioindicator of mercury pollution. Analysis of the test results data is presented in descriptive statistics. The results of this study are (1) The waters of Lake Lebo are polluted by mercury, found in sediments and water, and enter the food chain, namely gerris. The mercury concentration in the inlet area is greater than the outlet area because it is closer to the pollutant source (2). Gerris can be used as a bioindicator of mercury pollution in Lake Lebo Taliwang because it can accumulate heavy metals. It meets the criteria of bioindicator organisms and is very strongly correlated with water. The finding suggests that the local government makes regulations regarding mercury metal pollution in Taliwang Lake because mercury metal can enter other food chains and is toxic to living things.